A phenomenological model for the collective landing of bird flocks - Daruka, István (The Royal Society, 2008)
A three-dimensional phenomenological model was developed to describe the collective landing of bird flocks. The employed individual based model included the landscape (as an external field) and a continuous internal variable G, to characterize the landing intent of the birds. The birds' interaction with the landscape was coupled adaptively to their landing intent. During the flight, a sharp crossover is observed in the dynamics of the landing intent, i.e. from the initial, non-landing state (small G) to the landing state (large G) that was terminated by the landing of the flock. In the model, the landing process appears to be a highly concerted, collective motion of the birds, in agreement with the field observations.